Validating the National Coastal Climate Change Vulnerability Assessment’s inundation and erosion layers for the KwaDukuza Municipality, KwaZulu-Natal, South Africa - Law, Jessica (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPhil)--Stellenbosch University, 2023.